Optimal uptake rates for initial treatments for cervical cancer in concordance with guidelines in Australia and Canada: Results from two large cancer facilities. Issue 4 (August 2015) - Kang, Yoon-Jung; O'Connell, Dianne L.; Tan, Jeffrey; Lew, Jie-Bin; Demers, Alain; Lotocki, Robert; Kliewer, Erich V.; Hacker, Neville F.; Jackson, Michael; Delaney, Geoff P.; Barton, Michael; Canfell, Karen
Highlights: We estimated optimal rates for all initial treatment modalities for cervical cancer. We compared the optimal and the observed rates in Australia and Canada. The overall optimal treatment rates are largely dependent on the stage distribution. Observed surgery rates were similar to the estimated optimal rates. Observed radiotherapy, chemotherapy and chemo-radiotherapy were under-utilised. Abstract: Background: Prior work estimating optimal treatment utilisation rates for cervical cancer has focused on radiotherapy or chemotherapy, using proportions of patients with clinical indications for specific treatment strategies which were obtained from the published literature. Objectives: To estimate optimal uptake rates for surgery, radiotherapy, chemotherapy and chemo-radiotherapy for cervical cancer treatment in Australia and Canada, and to quantify the differences in the optimal and the observed treatment utilisation rates in a large cancer facility from each country. Methods: A decision tree was constructed to reflect treatments according to guidelines and current practice (in 1999–2008) in each setting. Detailed patterns of care data from a large cancer facility in each country were obtained, and the observed stage distribution and proportions of patients with each clinical indication were used as inputs. Results: The estimated overall optimal treatment rates for cervical cancer in Australia and Canada differed, largely due to the difference in the stage distribution at diagnosis in the two settings; 72% vs 54% with FIGO IA-IIA disease, respectively. The estimated optimal rates for surgery, radiotherapy, chemotherapy and chemo-radiotherapy in Australia were 63% (95% credible interval: 61–64%), 52% (53–56%), 36% (35–38%) and 36% (35–38%), respectively. The corresponding rates in Canada were 38% (36–39%), 68% (68–71%), 51% (49–52%) and 50% (49–51%), respectively. The absolute differences between the optimal and the observed rates were similar between the two settings; the absolute differences for chemotherapy and chemo-radiotherapy uptake were more pronounced (9–15% less than optimal) than those for surgery and radiotherapy uptake (within 5% of optimal). Conclusions: This is the first study to use detailed patterns of care data in multiple settings to compare optimal and observed rates for all cervical cancer treatment modalities. We found optimal treatment rates were largely dependent on the overall stage distribution. In Australia and Canada, observed surgery rates, as measured in the two large cancer facilities, were similar to the estimated optimal rates, whereas radiotherapy, chemotherapy and chemo-radiotherapy appeared to be under-utilised.